Studi Pemetaan Dakwah dalam Penyuluhan Agama - Kusnawan, Aep (UIN Antasari Banjarmasin, 2017)
Religious counselors are like doctors who will give medicine, so he must make a thorough diagnosis in order to have a picture of the right conditions, what diseases suffered by patients, what medications are right, and what level of health might be built with the drug.Similarly, the extension of religion, if it is intended to improve the condition of society, it is necessary for him to start the activity by first knowing the objective condition of the object of dawah, which then followed up with various activities of dawah appropriate, effective and efficient. Efforts to determine the objective conditions madu it, the authors do through research mapping dawah in Bandung.This research was conducted on the academic community of Dakwah Faculty who actively conducted mapping of dawah in Bandung. Using qualitative methods. Through interviewing techniques and documentation.The results showed that mapping of dawah is a very basic need in religious education activities. It is useful to facilitate the analysis of religious counseling objects, so that the counselor can properly present the material, methods and media used in religious counseling, in accordance with the conditions and needs of the local community. With that mapping, religious counseling basically will not only shaped the message of Islamic teachings, but is moving towards religious social change.